Medical application of innovative nuclear-physical technologies - Бондар, Віра Михайлівна (Eastern-European Journal of Enterprise Technologies, 2013)
Heart and cancer-related diseases are considered to be one of the biggest problems of today’s health world. Therefore, it is important to perform fundamental research of human tissues and external biological influence on these tissues, as well as develop and implement new innovative instruments of applied physics for diagnosis and treatment of heart and cancer diseases. This paper presents overview of modern technical methods based on using ionizing radiation for medical purposes. In particular, new effective instruments of nuclear and high energy physics are considered in context of their implementation for the diagnosis and cancer treatment. Physical principles and main characteristics of PET imagining are discussed, as well as examples of successful implementation of protons (heavy ions) for the treatment are presented. A detailed overview of new advanced detector technologies and codes for modeling the processes of penetration of radiation with the matter is given. Perspective ideas of new nuclear instrumental technologies and methods are discussed. The problem of interconnection of fundamental research and bio-medical field is discusses, considering this as one of the obligatory conditions for successful implementation of new research instruments for advanced medical diagnosis technologies and treatment.